Annual Report 2008 (2008)
This 2008 Annual Report records the achievements, outreach activities, and student honors work of the Eastern Illinois University's Lumpkin College of Business and Applied Sciences. It also includes reports from the School of Business, the School of Family and Consumer Science, the School of Technology, and the department of Military Science.https://thekeep.eiu.edu/lumpkin_annualreports/1014/thumbnail.jp